Microbial Co-occurrence Network and Fermentation Information of Natural Woody-Plant Silage Prepared With Grass and Crop By-Product in Southern Africa - Du, Zhumei; Yamasaki, Seishi; Oya, Tetsuji; Nguluve, Damiao; Euridse, Denise; Tinga, Benedito; Macome, Felicidade; Cai, Yimin (Frontiers in Microbiology, 2022)
To facilitate the use of woody plant (WP) as a natural biomass resource to address the shortage of feed for ruminants in the tropics, we use PacBio SMRT sequencing to explore the microbial co-occurrence network and silage fermentation of gliricidia and leucaena prepared with Napier grass (NG) and corn stover (CS) in Southern Africa. Based on dry matter, the crude protein contents of WP are as high as 25%. Compared with NG, the addition of CS speed up the dynamic succession of microorganisms in the silage fermentation process from Gram-negative bacteria to Gram-positive bacteria, and promoted Lactiplantibacillus plantarum to become the dominant community and enhanced the metabolic pathways of lactic acid and citric acid, thus improved the fermentation flavor and quality of WP silage. WP can be mixed with CS to make high-quality silage, which can alleviate the shortage of feed and promote local animal production.